Analysis of Workload and Needs of Distribution Staff Nutrition Installation at PKU Muhammadiyah Sukoharjo Hospital - Azhari, Salma Widya; Triswaty, Tiar; Widiyaningsih, Endang Nur; Syafaah, Hannisa (Prosiding University Research Colloquium, 2023)
The hospital provides services intended for the recovery of its patients without neglecting other promotive, preventive and rehabilitative roles, one of which is through nutrition service activities in the hospital. Food distribution is a series of food delivery activities according to the type of food and the number of patients. The purpose of this study was to conduct research to analyze the workload and calculate the need for distribution personnel at the Nutrition Installation at PKU Muhammadiyah Sukoharjo Hospital. This study used a qualitative research design with an observational design. Purposive sampling technique was used for sampling. The workload that has been obtained is then used to calculate workforce requirements using the Work Load Indicators Staff Need (WISN) method. Analysis of the workload of distribution workers in the morning shift and afternoon shift respectively amounted to 86.33% and 73,2% which is in the heavy category because it exceeds 80%. To achieve a balanced need for distribution personnel, it is necessary 10 distribution personnel.